Ethnicity, Marriage and Family Income - Julia Anna Matz (University of Bonn, Center for Development Research (ZEF), 2013)
This study adds a microeconomic perspective to the discussion on ethnic diversity and economic performance in developing countries by investigating the motivation for intra-ethnicity marriage in rural Sub-Saharan Africa. Specifically, the paper proposes that ethnic similarity between spouses enhances economic outcomes through a shared agricultural production technology. Furthermore, the framework suggests that the probability of marriage within the same ethnic group is positively related to the size of the group due to frictions in the marriage market: Search costs for co-ethnic spouses are larger the smaller the group. The theoretical propositions are supported using Ethiopian rural household data by demonstrating that inter-ethnicity marriage of the household head has adverse implications for family income. The negative effect is robust to controlling for lagged income and initial conditions, present when investigating the link with changes in family wealth, and persists in additional sensitivity checks.
Keywords: D10; J12; O12; 330; Ethnic Diversity; Heterogamy; Marriage; Family Income